Complex Word Processing in Teenage Poor Readers- Does Morphological Knowledge Help or Hinder? - Henry, Regina (My University, 2012)
Complex Word Processing in Teenage Poor Readers- Does Morphological Knowledge Help or Hinder?
Abstract
This longitudinal study addressed development of morphological awareness in fourteen-to-seventeen-year-olds reading disabled (RD) high school students enrolled in the Wilson Reading Program (Wilson, 1989). Our lexical decision experiment and reading fluency assessment took place in the first (session 1) and last months (session 2) of the school year that included training with morphologically complex English words. The lexical decision stimuli were composed of derived (critical), compound (bathtub) and pseudo-complex (postpone) words from the training program (trained words), matched complex words not in the training program (untrained words), and nonwords. Accuracy and response times were compared between sessions, and with a comparison group of age-matched typical readers. The RD group did not demonstrate large post-training gains in reading fluency, but, there were significant improvements in accuracy and speed in visual lexical decision. These improvements did not extend to auditory lexical decision, suggesting that the observed improvements in visual word recognition were a result of the training, and not a practice effect due to multiple testing sessions. Additionally, there was post-training improvement in both trained and untrained words implying that the RD students were able to generalize their acquired knowledge of grapheme-phoneme mappings and morphological processing to novel words. Both the RD and comparison group demonstrated the same hierarchy of accuracy and response time patterns for complex words suggest a processing advantage for visually presented derived and compound words that is not skill dependent.
Keywords: reading deficits; adolescents; morphology; remedial reading intervention; complex words; lexical decision; Reading and Language; Reading and Language